Fiscal Safeguards. (Policy Papers; Policy Paper ;, 2012)
This paper notifies the Executive Board of a pilot exercise for fiscal safeguards. The pilot will be conducted by the Fiscal Affairs Department and will cover a limited number of large budget financing cases over the next twelve months. Contrary to the existing safeguards assessment for central banks, participation in this exercise will be voluntary but will follow similar procedures in terms of confidentiality.